2018
DOI: 10.1016/j.eururo.2017.08.035
|View full text |Cite
|
Sign up to set email alerts
|

The Phase 3 COU-AA-302 Study of Abiraterone Acetate Plus Prednisone in Men with Chemotherapy-naïve Metastatic Castration-resistant Prostate Cancer: Stratified Analysis Based on Pain, Prostate-specific Antigen, and Gleason Score

Abstract: Treatment with abiraterone acetate and prednisone (compared with treatment with prednisone only) for metastatic castration-resistant prostate cancer increased survival in all patients in the study regardless of pain, prostate-specific antigen levels at the start of treatment, and Gleason score at primary diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 26 publications
1
33
1
3
Order By: Relevance
“…One of the purposes of the STABEN trial was to assess whether the potential advantage associated with statin use could be related to their known cardiovascular and cerebrovascular protective effect, of particular potential importance in an elderly population receiving abiraterone – an agent with known cardiovascular toxicity [ 22 ]. In the present retrospective study, multivariable models that included known prognostic factors in prostate cancer (e.g., baseline PSA levels, hemoglobin levels, Gleason score, alkaline phosphatase and LDH levels [ 23 ], visceral involvement [ 24 ] and neutrophil to lymphocyte ratio [ 25 ]) revealed that statin use was associated with a 53% reduction in the risk of all-cause mortality, and a 57% reduction in the risk of prostate cancer-specific mortality. It also appeared that statin co-administration increased the odds of having an early >30% PSA decrease, which is consistent with our previously reported findings and adds strength to the hypothesis of a potential synergism with abiraterone/enzalutamide.…”
Section: Discussionmentioning
confidence: 97%
“…One of the purposes of the STABEN trial was to assess whether the potential advantage associated with statin use could be related to their known cardiovascular and cerebrovascular protective effect, of particular potential importance in an elderly population receiving abiraterone – an agent with known cardiovascular toxicity [ 22 ]. In the present retrospective study, multivariable models that included known prognostic factors in prostate cancer (e.g., baseline PSA levels, hemoglobin levels, Gleason score, alkaline phosphatase and LDH levels [ 23 ], visceral involvement [ 24 ] and neutrophil to lymphocyte ratio [ 25 ]) revealed that statin use was associated with a 53% reduction in the risk of all-cause mortality, and a 57% reduction in the risk of prostate cancer-specific mortality. It also appeared that statin co-administration increased the odds of having an early >30% PSA decrease, which is consistent with our previously reported findings and adds strength to the hypothesis of a potential synergism with abiraterone/enzalutamide.…”
Section: Discussionmentioning
confidence: 97%
“…Other issues discussed in relation to mCRPC included the following: whether the clinical benefits of starting treatment for mCRPC earlier (e.g. whilst patients are asymptomatic or have a lower Gleason score or PSA level) are sufficient to justify the additional cost. a comparison of approaches used across the region to manage skeletal‐related events in men with mCRPC receiving ADT. …”
Section: The Apac Apccc 2018 Outcomesmentioning
confidence: 99%
“…Other issues discussed in relation to mCRPC included the following: [32] are sufficient to justify the additional cost.…”
Section: Other Issues Related To the Management Of Mcrpcmentioning
confidence: 99%
“…Ein Unterschied zwischen FTh-und STh-Patienten ergab sich aber für das Gesamtüberleben (OS). Diese Ergebnisse stehen im Gegensatz zur COU-AA-302-Posthoc-Analyse, bei der OS, rPFS, Zeit bis zur Chemotherapie und Zeit bis zum Opioidgebrauch bei asymptomatischen mCRPC-Patienten mit PSA-Werten < 80 ng/ ml zu Beginn der Behandlung und einem GS von < 8 bei Primärdiagnose im Vergleich zu Patienten mit fortgeschrittenem PSA oder Schmerzniveau oder einem GS von ≥ 8 länger waren [19].…”
Section: Diskussionunclassified